2007
DOI: 10.1373/clinchem.2007.089524
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Testing for Lupus Anticoagulants: A Review of Issues Affecting Results

Abstract: Background: Lupus anticoagulants (LA) are a heterogeneous class of immunoglobulins. Persistent LA positivity is a risk factor for the occurrence and recurrence of venous/arterial thromboembolism and/or pregnancy morbidity and qualifies the patient for anticoagulation therapy. The laboratory diagnosis for LA that is used for crucial decision-making about the optimal duration of the therapy rests entirely on diagnostic criteria. These criteria are based on the prolongation of phospholipiddependent tests not corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 46 publications
2
85
0
Order By: Relevance
“…In contrast, the activated partial thromboplastin time (aPTT), the kaolin clotting time (KCT), and the silica clotting time (SCT) assays activate the contact activation and common coagulation pathways. 11 The International Society of Haemostasis and Thrombosis (ISTH), 12 the British Committee for Standards in Haematology (BCSH), 13 and the Clinical and Laboratory Standards Institute (CLSI) 14 recognize that a single assay that can detect all individuals who are truly positive for LAC does not currently exist, so in their respective guidelines, they recommend that 2 different assays with distinct performance principles be undertaken to detect LAC. 15 A recent survey in Australia found that most hematology laboratories perform the dRVVT and aPTT LAC assays and 1/3 also use the KCT method.…”
Section: Lac Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the activated partial thromboplastin time (aPTT), the kaolin clotting time (KCT), and the silica clotting time (SCT) assays activate the contact activation and common coagulation pathways. 11 The International Society of Haemostasis and Thrombosis (ISTH), 12 the British Committee for Standards in Haematology (BCSH), 13 and the Clinical and Laboratory Standards Institute (CLSI) 14 recognize that a single assay that can detect all individuals who are truly positive for LAC does not currently exist, so in their respective guidelines, they recommend that 2 different assays with distinct performance principles be undertaken to detect LAC. 15 A recent survey in Australia found that most hematology laboratories perform the dRVVT and aPTT LAC assays and 1/3 also use the KCT method.…”
Section: Lac Assaysmentioning
confidence: 99%
“…This procedure may cause loss of VWF and consequently factor VIII, leading to artificial prolongation of coagulation tests responsive to factor VIII, namely aPTT. 11 For this reason, plasma filtration is no longer recommended.…”
Section: Lac Assays Preanalytic Considerationsmentioning
confidence: 99%
“…37 The mixing studies involve combining the patient's plasma with normal plasma (1:1) and assessing the influence of this procedure on clotting time, the theoretical underpinning being that if prolongation of clotting time is the result of a coagulation factor deficiency, it will correct to normal, whereas with LA, correction requires larger volumes of normal plasma. 33 A number of methods have been proposed by which this step can be interpreted, 36 the most robust being the calculation of the index of circulating anticoagulant, initially proposed by Rosner et al 38 To determine whether the inhibitor is phospholipid-dependent, the platelet-neutralization procedure, which uses either washed platelets activated with calcium ionophore or platelets lysed by repeated freeze-thawing (leading to the exposure of anionic phospholipid surfaces), is commonly used. 33 Correction of the clotting time will occur in the presence of LA.…”
Section: Overview Of the Assays Lupus Anticoagulantmentioning
confidence: 99%
“…35 One of the screening tests undertaken should use activation of the intrinsic pathway of coagulation (eg, aPTT or kaolin clotting time) and the other the direct activation of factor X (eg, dRVVT). 36 Local reference ranges should be established for each LA method used and for each coagulometer. 37 The mixing studies involve combining the patient's plasma with normal plasma (1:1) and assessing the influence of this procedure on clotting time, the theoretical underpinning being that if prolongation of clotting time is the result of a coagulation factor deficiency, it will correct to normal, whereas with LA, correction requires larger volumes of normal plasma.…”
mentioning
confidence: 99%
See 1 more Smart Citation